Climatic signals in lacustrine deposits of the Upper Yacoraite Formation, Western Argentina: Evidence from clay minerals, analcime, dolomite and fibrous calcite. Issue 5 (18th February 2020) - Gomes, João Paulo B.; Bunevich, Rodrigo B.; Tonietto, Sandra N.; Alves, Daisy B.; Santos, Julice F.; Whitaker, Fiona F.
Abstract: Authigenic clays are an important control on reservoir quality in lacustrine carbonates but remain challenging to predict. Lacustrine depositional systems respond to climatic variations in rainfall, surface runoff and groundwater input, and evaporation, and result in rapid and frequent changes in lake volume; this is expressed through changing water depth and shoreline position. In the upper portion of the Early Palaeocene Yacoraite Formation of the Salta Basin in Argentina, extensive lacustrine deposits were deposited during the sag phase of rifting. Prior high‐resolution stratigraphic studies have suggested that climatic factors control microbial carbonate sequences within a 'balanced fill' lake, with variation in the lake level having a major influence on facies association changes. This study characterizes the evolution of facies and mineralogy within the Yacoraite Formation, focusing on the distribution of clay minerals, making a link between the high, medium and low‐frequency sequence stratigraphic cycles. The low‐frequency transgressive hemicycle of the upper portion of the Yacoraite Formation is comprised of abundant siliciclastic facies, suggesting a wetter period. Microbialites occurring in this interval are coarse‐grained and agglutinated. Detrital clay minerals such as illite and chlorite and associated siliciclastic sediments were input to the lake during high‐frequency transgressive periods. During high‐frequency regressive hemicycles, sedimentation was dominated by carbonate facies with Ca‐rich dolomite and the authigenic clays are comprised of chlorite/smectite mixed‐layers. By contrast, the low frequency regressive hemicycle records fine‐grained agglutinated microbialite with horizons of fibrous calcite, more stoichiometric dolomite, barite and authigenic magnesian smectite. This indicates elevated ion concentrations in the lake under intense evaporation during an arid period. Understanding the conditions that are favourable for formation and preservation of authigenic clays within the lacustrine environment can improve understanding of reservoir quality in comparable economically important deposits.